Design of a wireless ureteropyeloscope - Ncube, Mkhokheli (Division of Biomedical Engineering, 2015)
Ureteroscopy is a form of endoscopy that concerns itself with the urinary system. Flexible ureteropyeloscopes are instruments used to access the urinary system for diagnostic and therapeutic procedures. An average ureteropyeloscope requires a repair for every 3 to 13 hours of use, or alternatively 6 to 15 procedures. Therefore, there is a need to increase the durability of the ureteropyeloscope to lower the frequency of repairs required. In addition, the number of cables in the workspace needs to be reduced for improved handling by the clinician. The present study details the design of an ureteropyeloscope, which is modelled after currently existing instruments. Current endoscopes use fibre-optics for lighting area of interest as well as image acquisition. However, the ureteropyeloscope discussed was developed with a camera at the distal end of the insertion tube as its image acquisition system. The images captured were transmitted to a monitor for viewing via a wireless transmission module. The ureteropyeloscope discussed in the study was aimed at increasing the durability of the deflection unit of the ureteropyeloscope, with primary component made of nitinol, and reducing the number of cables around the workstation by using wireless means to transmit images from image acquisition system to monitor.